AGRARIS : Assessment the Impact of Asean Free Trade Area (AFTA) on Exports of Indonesian Agricultural Commodity - Heri Akhmadi (Fakultas Pertanian UMY, 2017)
AFTA, Gravity Model, Agricultural Exports, JEL Classifications: F15, C23, Q17